Solow sustainablility with varying population levels - John M. Hartwick (Queen's University, Department of Economics, 2021)
We take up three variants of Solow [1974], each with population change endogenous. When each model exhibits sustainability the same three conditions are satisfied: (i) investment in produced capital is funded by resource rents plus "extra" saving, (ii) "extra" saving funds the same two gaps related to population increase and (iii) Hotelling's Rule is satisfied. We focus attention on condition (ii) here. The Stollery variant involves warming caused by current hydrocarbon extraction.
Keywords: Q32; 330; Sustainability; population increase; funding gaps